Inadequacies in the water reforms in the Kyrgyz Republic: an institutional analysis - Ul-Hassan, Mehmood; Starkloff, R.; Nizamedinkhodjaeva, Nargiza N. (International Water Management Institute, 2004)
This report analyzes the evolving water-management institutions and their performance of five core water management functions, in the context of the ongoing economic and agrarian reform in the Kyrgyz Republic. These core water-management functions are, operation of water systems, maintenance, resource mobilization, conflict resolution and organizational management. The report also identifies key issues and challenges that constrain effective stakeholder participation in water-resources management.